CARA PENENTUAN KELAS KUAT ACUAN BAMBU PETUNG - Oka, Gusti Made (MEKTEK, 2005)
Wood use in civil buildings has shown increasing demand whether for structural or non structural means. The demand itself can not be fulfilled because on the lack of lumber woods in large diameter. On the other hand, bamboo has not been optimally exploted althougth research results have shown that bamboo has strength and better performance compared to other building materials. This research was aimed to reveal the physical and mechanical properties of bamboo Petung. Preliminary research was made the physical and mechanical properties specimens bamboo Petung, which following the ISO 3129-197 standard test method. The result experiment showed that bamboo modulus of elasticity (MOE) obtained was 13257.65 MPa, therefore could be classified as strength class E13. The result of mechanical way test showed that modulus of rapture(MOR), the tensile strength, compression strength parallel, compression strength upright, the shear strength were 29 MPa, 27 MPa, 33 MPa, 11 MPa and 5 MPa